2020
DOI: 10.2169/internalmedicine.4588-20
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability-high Intrahepatic Cholangiocarcinoma with Portal Vein Tumor Thrombosis Successfully Treated with Pembrolizumab

Abstract: A 60-year-old man presented with postoperative recurrence of intrahepatic cholangiocarcinoma with right portal vein tumor thrombosis (PVTT). After failure of standard chemotherapy, a liver biopsy showed that his microsatellite instability (MSI) status was high. Treatment with the immune checkpoint inhibitor (ICI) pembrolizumab was commenced, which resulted in a partial response and resolution of the PVTT. There were no significant immune-related adverse events. According to recently published reports, the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Recently, it has been reported that immune checkpoint inhibitor (pembrolizumab) was effective in MSI-H patients with tumor thrombosis. This re ects the relationship between tumor thrombus and MSI and tumor immune microenvironment (31). Consistent with the previously studies, we found that CTNNA3 and FRMPD4 were positively correlated with MSI, as well as with immune microenvironment and immune cell subtype in ltration.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been reported that immune checkpoint inhibitor (pembrolizumab) was effective in MSI-H patients with tumor thrombosis. This re ects the relationship between tumor thrombus and MSI and tumor immune microenvironment (31). Consistent with the previously studies, we found that CTNNA3 and FRMPD4 were positively correlated with MSI, as well as with immune microenvironment and immune cell subtype in ltration.…”
Section: Discussionsupporting
confidence: 92%
“…Few cholangiocarcinoma cases have reported response to pembrolizumab; however, these tumors were microsatellite unstable or mismatch repair genes (MMR) deficient and only one case achieved pCR with pembrolizumab treatment alone [15][16][17][18]. Conversely, our patient was pMMR and MSS but TMB-H. TMB has emerged as an independent predictive biomarker for response to pembrolizumab monotherapy in patients with previously treated, recurrent, or metastatic advanced solid tumors [19,20].…”
Section: Discussionmentioning
confidence: 66%
“…Only three case reports exist of MSI‐high advanced cholangiocarcinoma treated with pembrolizumab 9‐11 . All cases showed a good response and maintained a PR during pembrolizumab treatment.…”
Section: Discussionmentioning
confidence: 99%